The Interactive Effect of Lead Acetate and Endurance Training on the Brain-Derived Neurotrophic Factor and Malondialdehyde Levels in Rats Cortex - S Hosseinzadeh (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Studies show that the moderate intensity exercise reduces the oxidative stress and increases the neurotrophin levels in brain, but less attention was given to the examination of exercise-induced neuroprotection after administration of lead acetate. The purpose of this study was to investigate the effects of 8 week endurance training on the brain-derived neurotrophic factor (BDNF) and malondialdehyde (MDA) levels in rats cortex exposed to lead acetate.METHODS: In this experimental study, 40 male Wistar rats, 50 days old with average weight of 250±3.79 g, were randomly divided into four groups included the base, control, exercise+lead and lead groups. The exercise training protocol consisted of running on a treadmill for 8 weeks training (15-22 m/min, 25-64 min). Exercise-lead and lead groups received 20 mg/kg lead acetate and sham group received 30 mg/kg of ethyl oleate peritoneally for 8 weeks. BDNF and MDA levels in cortex were measured by ELISA and TBARS methods, respectively. FINDINGS: Although, induction of lead acetate didn’t lead to significant change in cortical BDNF levels in lead group in compared to the control (1.93±1.26 in lead group in comparison to 1.78±1.13 ng/mg protein in control) but caused a significant increase in MDA levels in cortex in compared with control group (0.61±0.07 in lead group in comparison to 0.31±0.05 nmol/mg protein in control) (p values for BDNF and MDA: p=0.994 and p=0.000, respectively), versus the 8-week training reversed this process so that, caused insignificant increase in BDNF (2.98±1.39 in lead group in comparison to 1.93±1.26 ng/mg protein in control) and significant reduction in cortical MDA in training group in compared to lead group (0.5±0.04 in lead group in comparison to 0.61±0.07 nmol/mg protein in control) (p values for BDNF and MDA: p=0.207, p=0.048, respectively).CONCLUSION: The results of this study showed that although, regular exercise didn’t increase the BDNF significantly, but it can strengthen the brain’s defense structure against air pollutants through preventing BDNF reduction and improving oxidant/antioxidant process.